A study on corrosion of reinforcement in concrete and effect of inhibitor on service life of RCC - Kumar V.; Singh R.; Quraishi M.A. (My University, 2025)
Cement concrete has clearly emerged as the material of choice for the construction of a large number and variety of structures in the world today. Literature on reinforcement corrosion in concrete structures, its mechanism and factors affecting corrosion of steel in concrete are available. Extensive research work has been devoted to develop models that predicts the time for corrosion initiation. The study reveals that though Calcium palmitate and its combination withcalcium nitrite reduces the concrete strength but inhibition to the corrosion of the rebar increases the service life of the Reinforced concrete by 8 to ten times.